Women and Urbanisation in the Federal Capital Territory, Abuja, Nigeria - Audu, Mohammed S.; Sule, Hasiyah A. (ABUAD Journal of Social and Management Sciences, 2024)
This study examines women's role in the urbanisation of the Federal Capital Territory (FCT), Abuja. From the standpoint of feminist theory, urbanisation is believed to create expanded opportunities for the general populace as well as for women, who typically face discrimination in rural economies. However, the initial FCT master plan ended up being distorted by the dynamics and complexities of Abuja's urbanisation and growth process over time, which is driven by political and economic realities. There are drawbacks to urbanisation in civilisations with strong sociocultural norms and values, such as the fact that women must endure various forms of gender inequality, discrimination, and exclusion, particularly in the political sphere, which present significant difficulties. This study makes use of secondary data to demonstrate how the FCT's 2003 reconstruction to its original Master Plan provided chances for active participation in which women were included for both native people and newcomers. In a similar vein, the Federal Capital Development Authority's (FCDA) and other local council offices, which hired indigenous people for their departments and agencies, significantly altered the way of life for women from being rural farmers to empowered workers. In order to address the issues facing women in the FCT, empowerment must be a multifaceted process that transforms the economic, political, social, psychological, and legal conditions of the weak (women). It must also aim to demolish cultural, traditional, and social norms that devalue, disempower, and dispossess women, with a primary goal of meeting their needs.